Avaliação em profundidade e ecologia política: o caso do Programa Fortaleza Cidade Sustentável (FCS) - Porto, Filipe Cavalcante (2024)
The present work aimed to analyze the particularities and implications of an environmental public policy, by undertaking an in-depth evaluation of the Fortaleza Cidade Sustentável (FCS) programme, between 2014 and 2024, looking at the politics as part of the implementation of managerialism in local public administration, and therefore as a way of realizing neoliberal rationality (Dardot and Laval, 2016). As specific objectives, the local socio-economic and political context in which the policy was created and implemented was analyzed, analyzing the role of municipal management as a provider of environmental policies, reflecting their own conceptions concerning the environment and sustainable development; the political-economic pressures and the implications of the public administration's management parameters in the context of local policies and their connection to the environmental policy studied were investigated. It was also sought to identify the existing conceptions among the social actors that are part of the public policy analyzed. It concerns a multidimensional policy, and, for this reason, it was decided to use the theoreticalmethodological perspective of in-depth evaluation based on Rodrigues (2016), since it allows us to understand the issues surrounding the programme, considering its socio-political and economic context, the involved agents, and their circumstances. From the methodological point of view, it is qualitative research, in which it seeks to achieve the proposed objectives through bibliographic and documentary research, as well as interviews with social actors directly related to the policy studied. It also used the perspective of content analysis (Bardin, 1977), carried out with the help of the qualitative data processing software IRaMuTeQ, to enrich the discussions about the intentionalities present in the discourses that permeate the policy studied. As a critical perspective guiding the environmental debate, we chose to work with Political Ecology (Souza, 2019), thus evidencing the political, economic, and social implications of management actions in conducting the program. Based on the analysis carried out with the development of the evaluation axes, it was found that there was a strong presence of objectives identified as public administration management practices aimed at efficiency and effectiveness in the public service provision, equally in the creation of urban business opportunities and in the strengthening of management instruments that enable the increase of municipal revenue, placing the urban environment at the service of economic development in the urban space of Fortaleza.